THE INFLUENCE OF INFORMATION TECHNOLOGY, HUMAN RESOURCES AND COMPUTER NETWORKS ON THE MARKETING INFORMATION SYSTEM (MSDM LITERATURE REVIEW) - Siregar, Mewarni (Dinasti International Journal of Digital Business Management, 2022)
Previous research is very important in a research or scientific article. Previous research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the Effect of Information Technology, Human Resources and Computer Networks on Marketing Information Systems, a literature study on Marketing Information Systems. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) Information Technology has an effect on the Marketing Information System; 2) Human Resources affect the Marketing Information System; and 3 Computer Networks affect the Marketing Information System.